2013
DOI: 10.1039/c3ra40857d
|View full text |Cite
|
Sign up to set email alerts
|

Double-headed nucleotides in DNA-zipper structures; base–base interactions and UV-induced cross-coupling in the minor groove

Abstract: Nucleic acids containing double-headed nucleotides with additional nucleobases attached to the 59(S)position of thymidine through a methylene linker are studied. The additional bases are oriented towards base-base interactions in the minor groove of the DNA-double helix. Two new examples with adenine or cytosine as the additional bases as well as an analogue with a 4N-methylpiperazine in the same position are introduced, and in a combined study with the original double-headed nucleotide containing two thymines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…4,5 In this context, an interesting modification is the addition of a second nucleobase to the nucleotide skeletonthe so-called double-headed nucleotide. 6 We have previously reported the synthesis and recognition properties of several double-headed nucleotides with the additional nucleobase attached to the 5´-, 2´or 5-position through various linkers, [7][8][9][10][11][12][13][14][15][16][17] while others have used the 4´-position or the 2´-N of amino-LNA as attachment points. 18,19 For the dU B design (Fig.…”
mentioning
confidence: 99%
“…4,5 In this context, an interesting modification is the addition of a second nucleobase to the nucleotide skeletonthe so-called double-headed nucleotide. 6 We have previously reported the synthesis and recognition properties of several double-headed nucleotides with the additional nucleobase attached to the 5´-, 2´or 5-position through various linkers, [7][8][9][10][11][12][13][14][15][16][17] while others have used the 4´-position or the 2´-N of amino-LNA as attachment points. 18,19 For the dU B design (Fig.…”
mentioning
confidence: 99%
“…Beside its biological functionality, DNA has emerged as a convenient scaffold for two-and three-dimensional objects in nanotechnology 1,2 and information storage. 3,4 Recently, we [5][6][7][8][9][10][11][12][13][14][15] and others [16][17][18][19][20] have examined the potential of introducing a second nucleobase onto the existing nucleotide scaffold as a means of increasing the molecular diversity of DNA. These so-called bis-headed or double-headed nucleotides enable various intra or extra-helical contacts depending on the location of the second nucleobase.…”
mentioning
confidence: 99%
“…In recent years, several double-headed nucleoside designs have been presented in the literature. [7][8][9][10][11][12][13] Our previous work has shown that depending on the site of attachment, the additional nucleobase can be positioned in the minor groove, [14][15][16][17] the major groove, [18][19][20] or the center of a DNA duplex. [21][22][23] In the latter case, given that the additional nucleobase is linked through a methylene to the 2'-position of 2'-deoxyuridine or arabinouridine (Figure 1, U X ), the doubleheaded nucleotide has been shown to behave as a condensed dinucleotide.…”
Section: Introductionmentioning
confidence: 99%